The Liberal Script: A Reconstruction - Michael Zürn; Johannes Gerschewski (The Liberal Script at the Beginning of the 21st Century: Conceptions, Components, and Tensions, 2024)
This contribution submits a specific description of the contemporary liberal script based on a sociological reconstruction. A script consists of a complex set of prescriptive and descriptive statements and a specific grammar that points to the relationship between them. We start by identifying the first layer of the liberal script, understood as the justificatory basis for developing additional components. Then, we discuss additional components that speak to societal, economic, political, and cross-cutting issues of a liberal script. Since there is no single, unambiguous thing called liberalism, we identify varieties of the liberal script, i.e. a class with differing ideas that show significant commonalities and overlaps. We do so by considering on the one hand a set of concepts that share a family resemblance, as Wittgenstein described. On the other hand, we carve out the most critical tensions between these concepts.
Keywords: 300; liberalism; liberty; individual self-determination; script; sociological reconstruction; family resemblance; tensions